Identitas Multikultural Salam-Sarani di Maluku sebagai Model Memelihara Integrasi Bangsa - Eklefina Pattinama (Program Pascasarjana UKIM, 2020)
There are many ethnic and sub-ethnic groups, religions, and ideologies in Ambon and Saparua islands. These pluralistic existences imply that differences are a core part of the society which can become a strength to live together, but also a threat to the society. Ironically, there is a tendency to manipulate these pluralistic existences to become provocative issues to raise tension in these societies. Therefore, this article aims to study how pluralistic societies such as people in Ambon and Saparua islands maintain national integrity through strengthening multicultural identity. By conducting field research and library study, the researcher found out that to develop a multicultural identity, one must have the ability to maintain self-narration. In self-narration, people must have the ability to develop consistent awareness about the continuity of self-biography. Besides, the very basic principle of people in Ambon and Saparua islands to maintain national integrity is through their daily activities as anak negeri which has shaped their religious special identity as Salam-Sarani.